The Influence of Transformational Leadership and Leader-Member Exchange (LMX) on the Performance of the Indonesian National Police at the Bengkulu Regional Police - Elvianus Laoli; Oscarius Yudhi Ari Wijaya (Transpublika Publisher, 2026)
The performance of the Indonesian National Police still faces challenges in the form of declining public trust, leadership issues, and disparities in the quality of working relationships between leaders and members, which have an impact on organizational performance and the quality of public services. The present research is designed to elucidate the nature of the relationships, both collective and individual, between specified leadership variables namely transformational leadership and Leader-Member Exchange (LMX) and the performance of personnel at the Bengkulu Regional Police (Polda Bengkulu). A quantitative paradigm is adopted, utilizing Multiple Linear Regression Analysis as the primary statistical technique to model and quantify these influences. SPSS output results, such as significance values (Sig.) and t-test or F-test values, are interpreted to draw conclusions about whether training and career development significantly influence the job satisfaction of police officers. Utilizing a simple random sampling method, 438 officers from the Bengkulu Regional Police were surveyed. A 7-point Likert scale questionnaire, disseminated via social media, served as the data collection instrument. Following validity and reliability testing to confirm the measurement tools’ accuracy and consistency, a t-test was conducted to evaluate partial hypotheses. The analysis revealed significant positive relationships, indicating that both transformational leadership and LMX are positively associated with police performance within this force. Strengthening transformational leadership and the quality of LMX relationships, supported by optimized internal management and digital transformation of services, are strategic factors in improving police personnel performance while strengthening public trust in the institution.